Upaya Penyelesaian Kredit Macet Dana Bergulir di Unit Pengelola Kegiatan (Upk) Kecamatan Jeumpa Kabupaten Aceh Barat Daya - Mahfuzah, Mahfuzah; Trisna, Nila (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2023)
Savings and loans revolving fund PNPM Mandiri Rural in the UPK Jeumpa District, Aceh Barat Daya Regency has been running since 2009 until now, but in its implementation many loans are experiencing bottlenecks because the borrower group does not use the loan in accordance with the agreement letter.The purpose of this study was to determine the efforts to resolve bad loans and the obstacles in the settlement of non-performing loans in revolving funds at the UPK Jeumpa District, Southwest Aceh Regency. This research is an empirical juridical research using descriptive analysis method that describes efforts to resolve bad loans.The results of this study indicate that the settlement of bad debts is carried out by the following mechanism, arrears in the first month are given a verbal warning to the group leader, if the first method does not work then a warning letter will be given three times in a row and if the debtor still does not have good intentions To pay off the credit, the UPK will make efforts to save the credit, namely the confiscation of the collateral. Furthermore, a negotiated settlement is carried out for debtors who have good intentions, namely by providing credit relief by extending the loan period. As for the obstacles in resolving bad loans, there are debtors who have bad intentions who intentionally do not complete their credit payments, the spread of the Corona Virus which has an impact on the community's economy, business failures that result in debtors having difficulty completing their loans, and the UPK's lack of firmness in imposing sanctions on debtors. or groups of borrowers who are in arrears, so that the debtor ignores the sanctions.Suggestions for the Activity Management Unit (UPK), to be more thorough, careful and careful in choosing groups to be given loans, and to collect regularly, in an effort to settle bad loans, the UPK should be more strict with debtors who violate the agreement by providing heavier sanctions so that the debtor feels deterred. And for the Women's Savings and Loans group (SPP) it is expected that they fulfill the agreements that have been made and mutually agreed upon so as not to cause problems in the future.